2019
DOI: 10.21873/anticanres.13270
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Following Anastomotic Leakage After Surgery for Carcinoma of the Distal Esophagus and Gastroesophageal Junction: A Systematic Review

Abstract: Background: Esophageal cancer is the ninth most common cancer. The only potentially curative treatment is surgical resection, which unfortunately is still associated with major complications, the most important being anastomotic leakage, currently with an overall rate of up to 26% morbidity. The aim of this systematic review was to evaluate the relationship between anastomotic leakage and recurrence of disease. Materials and Methods: A literature search was systematically performed. Seven out of 312 articles d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…Elderly esophageal cancer patients generally have co-morbidities and age-related physiological problems (6)(7)(8). Previous reports have shown that the postoperative surgical complication rates after esophagectomy are 30% to 70%, and the mortality rate is 1%-5% (9)(10)(11)(12). Given this situation, perioperative management might be difficult in elderly esophageal cancer patients.…”
mentioning
confidence: 99%
“…Elderly esophageal cancer patients generally have co-morbidities and age-related physiological problems (6)(7)(8). Previous reports have shown that the postoperative surgical complication rates after esophagectomy are 30% to 70%, and the mortality rate is 1%-5% (9)(10)(11)(12). Given this situation, perioperative management might be difficult in elderly esophageal cancer patients.…”
mentioning
confidence: 99%
“…The relationship between AL and long-term results after surgery for gastric cancer is still the subject of debate. Our group has recently published a review regarding the relationship between AL and oesophageal cancer, showing how, with a proper literature analysis, is it possible to highlight the relationship between AL and survival (17). A similar investigation was performed on colorectal surgery, concluding that AL after proctectomy for cancer is associated with worse long-term DFS and overall survival (18).…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that major complications (CD ! IIIa) are associated with postponement of adjuvant therapy and worse oncological outcomes, like local recurrences and shortened recurrence-free survival [7,8]. The majority of studies addressing the prevention of postoperative complications have concentrated on operation-specific risk factors (e.g., anastomosis technique).…”
Section: Introductionmentioning
confidence: 99%